Global burden of vertebral fractures from 1990 to 2021 and projections for the next three decades - Honghui Lei; Zebin Huang; Fangyong Wang; Tao Liu; Yang Yu; Sitong Su; Meiling Cheng; Haoyuan Chen (Journal of Orthopaedic Surgery and Research)
Abstract Background Vertebral fractures are linked to significant disability and mortality risks. Yet, existing studies on their global burden are outdated and lack predictive foresight. Methods Public data from the 2021 GBD study were analyzed to assess the global burden and epidemiological trends of vertebral fractures. The annual percentage change (EAPC) was calculated to represent temporal trends from 1990 to 2021. Machine learning was used to predict the global burden of vertebral fractures over the next 30 years. Results From 1990 to 2021, the global burden of vertebral fractures significantly decreased. The age-standardized incidence rates (ASIR) showed the largest decline in Eastern Sub-Saharan Africa (EAPC: -1.5; 95% CI: -2.0 to -1.0), while North Africa and the Middle East were the only regions to report an increase (EAPC: 0.3; 95% CI: 0.1 to 0.5). For age-standardized prevalence rates (ASPR), High-income Asia Pacific saw the steepest decline (EAPC: -1.4; 95% CI: -1.5 to -1.2), while the Caribbean experienced the largest increase (EAPC: 0.8; 95% CI: 0.4 to 1.3). Similarly, in terms of age-standardized years lived with disability rates (ASYR), the most substantial reduction occurred in High-income Asia Pacific (EAPC: -1.4; 95% CI: -1.5 to -1.3), with the Caribbean again showing the greatest rise (EAPC: 0.8; 95% CI: 0.3 to 1.2). Males generally exhibited higher age-standardized rates (ASRs) than females, although females aged 65–70 years old surpassed males. Predictive models suggest continued declines in global ASIR, ASPR, and ASYR by 2050. Conclusions Our study shows a steady reduction in the global burden of vertebral fractures from 1990 to 2021. Nevertheless, disparities remain across regions, with a positive correlation between ASRs with SDI.